ARTIFICIAL INTELLIGENCE AND NATIONAL SECURITY STRATEGY DEVELOPMENT - CHALLENGES AND PERSPECTIVES - Hatidza, Berisa Alil; Pavić, Aleksandar (National interest, 2024)
As a rule, the directions of development of the national security strategy are always aligned with vital national interests and modern achievements of society, which are imbued with modern challenges, risks and threats and available instruments of power. Monitoring global trends and the use of an adequate methodological approach enables the strategy to reflect a clear definition of national interests, ways of achieving them and the state's ability to achieve those interests using instruments of national power. Artificial intelligence through various forms of manifestation will significantly influence the development of future society. The implementation methodology will depend primarily on the needs and capabilities of the state. The goal of this work is to bring artificial intelligence closer to the professional public and to somehow place it in the focus of future considerations in the field of security and defense. Technology, which every day is becoming more and more present in all spheres of life, must find its role and place in strategic and doctrinal documents related to the defense of the state. Artificial intelligence must be integrated and operationalized as one of the starting points for creating a modern national security strategy, which is also the thesis of this expert work. The thesis clearly implies that the future national security strategy cannot be conceived without the concept of using artificial intelligence. The theoretical foundation of artificial intelligence is imbued in various scientific fields that primarily deal with automation and autonomous use of systems. Practical application found its basis in the gradual but comprehensive digitization of all spheres of life and society as a whole. From the point of view of national security, it is especially important to consider the impact in the development of autonomous weapon systems, the perspective of their use and the way they will shape modern armed conflicts.
Keywords: artificial intelligence; national security strategy; autonomous armed systems; factor; military forces; war; military system; resources